Peningkatan Pengetahuan dan Dukungan Masyarakat terhadap Persalinan Aman melalui Program PESAN CINTA (Peduli SayaNgi Calon Ibu BersaliN KiTa) di Wilayah Kerja UPTD Puskesmas Muara Komam Kabupaten Paser - Reni Yuli Astutik; Norkaya Norkaya (Yayasan Inspirasi El Burhani, 2026)
Introduction: Childbirth assisted by skilled health personnel in healthcare facilities remains one of the key indicators for reducing maternal and neonatal mortality. Although antenatal care coverage in the working area of Muara Komam Public Health Center is relatively high, the coverage of institutional delivery reached only 91.3%, which is still below the national target. This condition indicates the need for innovative community empowerment strategies to improve knowledge, family support, and community participation in promoting safe childbirth. Objective: The purpose of this service was to improve the knowledge of pregnant women, families, health cadres, and community leaders regarding safe childbirth in healthcare facilities through the implementation of the PESAN CINTA (Peduli SayaNgi Calon Ibu BersaliN KiTa) program. Method: This public service was conducted by employing a community empowerment approach through health education using a Health Education Unit (SAP), interactive lectures, discussions, question-and-answer sessions, leaflet distribution, pre-test and post-test evaluation, and the establishment of the PESAN CINTA WhatsApp Group as a sustainable communication and health education platform. The program was conducted on June 29, 2026, at Batu Butok Village Hall, involving 35 participants consisting of pregnant women, family members, health cadres, village officials, community leaders, religious leaders, and traditional birth attendants. Results: Participant attendance reached 100%. The average knowledge score increased from 55 in the pre-test to 85 in the post-test, representing an improvement of 30 points (54.5%). This finding indicates a substantial increase in participants' knowledge regarding safe childbirth, danger signs during pregnancy, birth preparedness, and the importance of delivering in healthcare facilities. In addition, the establishment of the PESAN CINTA WhatsApp Group strengthened communication among healthcare providers, pregnant women, families, health cadres, and community stakeholders, thereby supporting the sustainability of health education and maternal health promotion Conclusion: The PESAN CINTA program effectively improved community knowledge, strengthened family involvement, and enhanced community commitment to supporting childbirth in healthcare facilities